The role of feedback on banking performance in determining strategic renewal paths: An exploratory study of the opinions of a sample of administrative leaders of private banks in the holy governorates of Karbala, Al-Najaf Al-Ashraf, and Babylon. - ميثاق هاتف الفتلاوي; زينب مكي البناء; قصي رزوقي عباس (Iraqi Journal for Administrative Sciences, 2024)
The objective of this research is to develop a clear xeplmation about the role playing by the performance feedback in diagnosing the strategic renewal path, which can be follow by private banks literature review regarding this subject has been carried out first. performance feedback which is considered the independent variable includes three dimensions, namely, (aspiration levels, risk taking, and organizational change), while addressing the strategic renewal dependent variable includes three dimensions, namely (content, context, and process). A random sample of (90) administrative leaders were selected from five private banks, (Baghdad, Middle East Investment, Gulf commercial Bank, Al-Mansour to investment, and the Iraqi Credit) in three provinces (holy city of Karbala, Najaf and Babil) . Questionnaire researcher has adopted a key tool to collect the data on the variables, and the results showed a correlation relationship and the impact of significant differences between performance feedback and strategic renewal. Find out and a set of recommendations came in the forefront to take advantage of the data performance feedback in determining the course of action and strategic renewal exploitative and exploratory which will be followed by banks when selecting the research sample and determining future ambition near and far levels and how to implement or achieve the type.